Juana La Beltraneja, Dynastic Fears, and Threats of Marriage (1475–1506) - Humble Ferreira, Susannah (Renaissance and Reformation / Renaissance et Réforme, 2020)
This article focuses on the life of Juana, the Excelente Senhora (excellent lady), between 1479 and 1506. Juana, widely known as La Beltraneja, was recognized by King Enrique IV of Castile (1454–74) as his legitimate daughter and successor despite claims that she had been conceived in an adulterous relationship between her mother Joana of Portugal and Beltrán de la Cueva. Although Juana lived in exile in Portugal from 1476 onward, her young age and unmarried status made her a powerful diplomatic weapon during the reign of the Portuguese king João II (1481–95). While she had professed as a nun and was nominally attached to the monastery of Santa Clara in Coimbra, her degree of seclusion waivered with the vicissitudes of Portugal’s foreign policy. Until 1522, she herself maintained the position that she was the rightful heir to the throne of Castile.